2015
DOI: 10.1680/stbu.13.00039
|View full text |Cite
|
Sign up to set email alerts
|

Strength of composite slabs with end-anchorage studs

Abstract: A finite-element model is proposed to simulate the load behaviour of composite slabs with studs as end anchorages.The model is verified against physical tests on 36 composite slabs with varying thickness of steel deck, diameter and height of the studs, concrete strength and length of shear span. The longitudinal shear strength contributed by the end anchorage is evaluated and compared with the design shear strength of individual studs proposed in different design codes. The contribution of studs as end anchora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…For composite slabs with end anchorage such as a welded stud, the slip at the profiled steel sheet-concrete interface can be reduced, whereas the bond between the steel sheet and concrete can be enhanced. Consequently, their strength and rigidity can be improved [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For composite slabs with end anchorage such as a welded stud, the slip at the profiled steel sheet-concrete interface can be reduced, whereas the bond between the steel sheet and concrete can be enhanced. Consequently, their strength and rigidity can be improved [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the shear strength of the composite slabs was mainly governed by the same property of the shear span. Based on an investigation of the effect of end-anchorage studs on the longitudinal shear strength of composite slabs, Chen et al [9] suggested that the contribution of the studs to the longitudinal shear bearing capacity of the composite slab was not simply an addition of the shear strengths of the individual studs.…”
Section: Introductionmentioning
confidence: 99%
“…Following an axial tension test on two notched rebar specimens to test the system, four-point bending tests of RC beams with embedded and external fibre optic strain sensors were carried out. While the results of the exercise did not produce a definitive conclusion on the utility of the proposed methodology, they do suggest that there is potential but considerable challenges remain to be overcome.The fifth paper (Chen et al, 2015) attempted to quantify the strength enhancement of the widely used profiled composite deck slabs by enforcing composite action between the steel deck and the concrete using shear stud connectors at the ends as anchorages. This is done by developing a finite-element model and validating against load testing of thirty six slabs.…”
mentioning
confidence: 99%
“…The fifth paper (Chen et al, 2015) attempted to quantify the strength enhancement of the widely used profiled composite deck slabs by enforcing composite action between the steel deck and the concrete using shear stud connectors at the ends as anchorages. This is done by developing a finite-element model and validating against load testing of thirty six slabs.…”
mentioning
confidence: 99%